Increased Mastery Of Arabic Vocabulary Through The Arabic Treasure Hunter Game: Peningkatan Penguasaan Kosa Kata Bahasa Arab Melalui Game Arabic Treasure Hunter - Azhar Alam; Kusnul Khotimah (MUHIBBUL ARABIYAH: Jurnal Pendidikan Bahasa Arab, 2021)
This study examines the success of Arabic learning activities using the Arabic Treasure Hunt Game learning model to improve students’ Arabic vocabulary mastery while knowing their perceptions of the learning model. This study uses a qualitative descriptive approach with data collection methods through observation and interview techniques. This research was carried out in Darusy Syahadah Boyolali Islamic boarding school with the research subject of I' dād Kulliyatil Mu'allimāt (IKM) of 42 students. The data analysis method is a qualitative analysis technique equipped with a bit of quantitative descriptive data. The results of this study indicate that (1) the Arabic Treasure Hunt Game can increase students' interest in learning Kulliyatil Mu'allimāt (IKM) in learning Arabic vocabulary. (2) The Arabic Treasure Hunt game can help students improve Arabic vocabulary mastery. (3) Students perceive the Arabic Treasure Hunt Game is an exciting game that can increase interest and enthusiasm for learning, facilitate mastering new vocabulary, and improve the ability to master Arabic vocabulary.